EXTENDED TAM TEST ON INDONESIAN SMEs’ FINTECH USERS & ITS FINANCIAL REPORTS - Wita Ramadhanti; Kurniawan Kurniawan; Mukhrodin Mukhrodin; Sri Murni Setyawati (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2020)
Indonesia have SME accounting standard that effective in 2018, but this standard adoption is not popular at that time. Hence recent fastest growing in financial technology adoption by food industries’ SME creating the need for having financial reports in order to make an exact reconciliation for the payment. This research wants to know whether this financial technology usage will lead to SME’s to make financial reports according to accounting standard. The model is designed to test the Extended Technology Acceptance Model (Extended-TAM). Population here is SME in food industry that on Grabfood list. 100 sample were drawn using purposive sampling for SME that uses OVO, a financial technology company that partnering with Grabfood. Data then analyzes using WarpPLS.This results is consistent with Extended TAM. The result also shows that adoption of FinTech will trigger SME to make better financial reports to make reconciliation process in billing easier.